Stochastic three-dimensional conditioned distribution of faults potentially responsible for the seismo-volcanic activity in Deception Island (South Shetland - Antarctica): VISHNU Project - Paredes, Carlos; Pérez-López, Raul; Giner Robles, Jorge Luis; Martínez Díaz, José Jesús; Vega, R. de la; Vicente, S. de; Queral, C.; González Casado, José Manuel (Sezione Scienze della Terra, Università di Siena, 2006)
Volcanism in Antarctica is a rare phenomenon in the present days, although many examples exist from the past. One of the most active emerged volcanoes in West Antarctica is Deception Island - the youngest stratovolcan in the South Shetland Islands. Strombolian and phreatomagmatic eruptions and explosions, driven by the tectonic forces in the Bransfield Rift and the water intrusion in magma chamber, produce the emergence of Deception Island since 780 ka ago. The morphology of the island is strongly controlled by the Caldera collapse (Port Foster) of the main magma chamber. Water pathways mainly follow fracture networks, that sustain stress conditions that promote the underwater flow. Steam and magma paths behave in the same way when rising to the surface. Geophysical and seismological evidences are in agreement with this hypothesis. This work presents the scientific research carried out during the first half of VISHNU Antarctic Project: entailing fieldwork in Deception Island. New fractal anisotropy and multifractal methodologies were used to produce a three-dimensional synthetic fracture network based on stochastic discrete fracture models. The simulated fracture field is conditioned to multi-scale surface fault data, local stress tensor, tectonic regime and geothermal, seismic and last volcanic datasets. Numerical modelling of thermal explosive regime on this fracture network according to faults characteristics is also studied. Ministerio de Educación y Ciencia (España) Depto. de Geodinámica, Estratigrafía y Paleontología Fac. de Ciencias Geológicas TRUE pub